Analysis of stacked V-slot loaded patch antenna for wideband application - Ansari J.A.; Singh P.; Dubey S.K.; Khan R.U.; Vishvakarma B.R. (My University, 2025)
The analysis of V-slot loaded antenna stacked with simple patch is carried out using equivalent circuit model. It is found that stacked patch antenna exhibits enhanced bandwidth that depends on various dimensions of the V-slot. The proposed theoretical results are compared with simulated and reported experimental results which are in good agreement. © 2008 Wiley Periodicals, Inc.